Resilience and sustainability in the production of Ullucus tuberosus under a biocultural approach in Andean communities - Aceldo Castillo, Marcela Fernanda; Meneses Quelal, Orlando (Comunicata Scientiae, 2025)
This article evaluates the agroecological and biocultural impact of Ullucus tuberosus cultivation in the Montúfar canton of Carchi province, Ecuador. Focusing on the "Producampo" Association, made up mostly of women, the research analyzes how they combine traditional and sustainable agricultural practices to ensure productive resilience and preserve biodiversity. Through qualitative methodologies such as interviews and participant observation, it was shown that 87.5% of farmers are women aged 39 to 75 who work more than 56 hours per week on their small plots, most of which are less than one hectare. Agroecological practices include the use of organic fertilizers, crop rotation, and natural methods for pest control. These actions not only minimize the use of chemical inputs but also strengthen sustainability and food security. Furthermore, bioculturalism plays a key role: farmers apply ancestral knowledge such as the lunar calendar and seed exchange, promoting social cohesion and adaptation to climate challenges. Despite limitations such as limited access to land, Ullucus tuberosus remains essential to the local economy and food supply. The study concludes by highlighting the need for public policies that support the integration of traditional knowledge with scientific innovations to strengthen agricultural sustainability and the empowerment of rural communities, especially women, within an inclusive development model.